Study of the use of traditional, complementary, and alternative medicine in Indian cancer patients - Nishitha Shetty; Paraashar Ravindranath Rai; Arpitha Shetty (Indian Journal of Medical and Paediatric Oncology)
Objectives: The use of alternative forms of medicine is well known in India, especially amongst cancer patients but there are very few studies that have investigated its usage and benefits. A study was conducted to determine the prevalence of the use of Traditional medicine, Complementary and Alternative Medicine (CAM) by cancer patients visiting a cancer care center. This study laid an emphasis on the predictors of use of CAM. Materials and Methods: This is an observational study conducted from March 2017 to May 2017 at a tertiary cancer care center. After obtaining informed consent, patients were handed a questionnaire and their responses were analyzed. Data analysis tools of Microsoft Office Excel 2007 were used for statistics. Results: A total of 407 patients took part in the study. The prevalence of traditional medicine and CAM was found to be 23.5% (96 patients). The mean duration of CAM use was 4.8 months (0.25 months–48 months). About 77% of the users had an education level below the upper primary level, of which 30.02% were illiterate. About 62.5% of the users were below poverty line. Nearly, 41.7% of the patients had not received any allopathic treatment before starting traditional medicine and CAM and did so for a mean duration of 4 months. About 53% of the patients who received some form of traditional medicine and CAM claim to have experienced some symptomatic benefits from its use. Nearly, 68.75% of the users were simultaneously receiving conventional anticancer therapy. Traditional medicine and CAM use was disclosed to the treating physician by 55% of the patients. Conclusion: Traditional medicine and CAM use have been shown to have a high prevalence among the less-educated and the economically backward sections of the society. There is not sufficient data to support the effectiveness and safety of traditional medicine and CAM. physicians have to acknowledge the increasing incidence of traditional medicine and CAM use in the population and actively inquire and educate the patients on its use.